Environmental taxation and redistribution concerns - Rafael Aigner (Max Planck Institute for Research on Collective Goods, 2011)
This paper shows how the optimal level of Pigouvian taxation is influenced by distributive concerns. With second-best instruments, a higher level of income redistribution calls for a lower level of Pigouvian taxation. More redistributionimplies that tax collection via the income tax creates higher distortions, which in turn makes revenues from Pigouvian taxation more valuable. Contrary to naive intuition, this reduces the optimal level of Pigouvian taxation. The social planner trades off environmental tax revenues against the marginal social damage and accepts a lower tax if the welfare created per dollar is higher. The paper also shows that the relation between levels of redistribution and Pigouvian taxation is reversed in first-best. It thus highlights that second-best Pigouvian taxes are very different from their first-best counterpart - despite apparently identical first order conditions.
Keywords: H21; D62; H23; 330; optimal income taxation; Pigouvian taxation; comparative statics; externalities; second-best; Einkommensteuer; Internalisierung externer Effekte; Ökosteuer; Optimale Besteuerung; Einkommensumverteilung; Second Best; Theorie